Beyond Divalent Copper: A Redox Couple for Sodium Ion Battery Cathode Materials. (19th March 2015) - Mason, Chad W.; Lange, Felix; Saravanan, Kuppan; Lin, Feng; Nordlund, Dennis
Abstract : A P2-layered oxide using copper as the active redox metal has been discovered. It has a composition of Na⅔ Cu⅓ Mn⅔ O2, and can withstand a thousand cycles, maintaining 61% of its original capacity. We demonstrate that copper can enable not only high voltage, but also excellent stability. This work opens up a new avenue of oxide design for high energy, cost effective battery systems.